Detection of pathogenic Vibrio spp. in foods: polymerase chain reaction-based screening strategy to rapidly detect pathogenic Vibrio parahaemolyticus, Vibrio cholerae, and Vibrio vulnificus in bivalve mollusks and preliminary results - Orlandina Di Maro; Yolande T.R. Proroga; Silvia Castellano; Anna Balestrieri; Federico Capuano; Enrico Arletti; Michelangelo Vietina; Melissa Bizzarri; Nicoletta Murru; Maria Francesca Peruzy; Daniela Cristiano (Italian Journal of Food Safety, 2024)
The majority of human diseases attributed to seafood are caused by Vibrio spp. and the most commonly reported species are Vibrio parahaemolyticus, Vibrio vulnificus, and Vibrio cholerae. The conventional methods for the detection of Vibrio species involve the use of selective media, which are inexpensive and simple but time-consuming. The present work aimed to develop a rapid method based on the use of multiplex real-time polymerase chain reaction (PCR) to detect V. parahaemolyticus, V. vulnificus, and V. cholerae in bivalve mollusks. 30 aliquots of bivalve mollusks (Mytilus galloprovincialis) were experimentally inoculated with two levels of V. parahaemolyticus, V. vulnificus, and V. cholerae. ISO 21872-1:2017 was used in parallel for qualitative analysis. The limit of detection of 50% was 7.67 CFU/g for V. cholerae, 0.024 CFU/g for V. vulnificus, and 1.36 CFU/g for V. parahaemolyticus. For V. vulnificus and V. cholerae, the real-time PCR protocol was demonstrated to amplify the pathogens in samples seeded with the lowest and highest levels. The molecular method evaluated showed a concordance rate of 100% with the reference microbiological method. V. parahaemolyticus was never detected in samples contaminated with the lowest level, and it was detected in 14 samples (93.33%) seeded with the highest concentration. In conclusion, the multiplex real-time PCR developed proved to be reliable for V. vulnificus and V. cholerae. Results for V. parahaemolyticus are promising, but further analysis is needed. The proposed method could represent a quick monitoring tool and, if used, would allow the implementation of food safety.